Form and Function of Aizuchi Japanese Native Speaker in Inaka Ni Tomarou! TV Serial - Iantika Humanjadna Dityandari; Bayu Aryanto (Universitas Diponegoro, 2020)
This study is intended to describe the form of aizuchi in the TV series Inaka Ni Tomarou! and find out the function of Aizuchi's speech based on the conversation context. The research data are the forms of aizuchi, which are used in a conversational context. This type of research is a qualitative descriptive study. The researchers found six forms of aizuchi: short speech, interjection speech, interjection, and short utterances, repeated short utterances, repeated speech partner utterance, short utterances, and repetition of speech partners. In the function, Aizuchi has seven functions: a continuer signal, an understanding signal, an approval signal, a signal indicating emotion, a signal to confirm, a rejection signal, and a filling signal.